Sustaining and Scaling Pedagogic Innovation in Sub-Saharan Africa: Grounded Insights For Teacher Professional Development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this commentary we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our work of over five years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. ‘OER4Schools’ integrates interactive pedagogy, Open Educational Resources (OER) and the use of mobile devices (where available). Our focus here is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through the use of OER. Our conclusions offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for future programme design and implementation.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Monday; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; STC-TLC; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; TL:Arabic; TL:English; TL:Translated; Teacher Professional Development; Technology Uses in Education; Telecommunications; TranslationGoingAhead; _C:Bangladesh BGD; _C:Brazil BRA; _C:Cambodia KHM; _C:Cameroon CMR; _C:China CHN; _C:Ethiopia ETH; _C:Ghana GHA; _C:India IND; _C:Japan JPN; _C:Kenya KEN; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:a; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found